Mental accounting in the housing market - Johan Almenberg; Artashes Karapetyan (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
We report evidence that salience may have economically significant effects on homeowners' borrowing behavior, through a bias in favour of less salient but more costly loans. We outline a simple model in which some consumers are biased. Under plausible assumptions, the bias may affect prices in equilibrium. Market data support the predictions of the model.
Keywords: D12; G14; G21; G32; 330; salience; housing market; household finance; co-op; capital structure; Konsumentenverhalten; Immobilienfinanzierung; Kapitalstruktur; Haushaltsökonomik; Schweden